Rudolf Nissen's years in bosphorus and the pioneers of thoracic surgery in Turkey - (:unkn) unknown (ELSEVIER SCIENCE INC, 2000)
Rudolph Nissen is one of the most distinguished pioneers in thoracic surgery, well known for his pneumonectomy operation performed for the first time in surgical history. He migrated to Istanbul like most of his contemporary colleagues, avoiding the fascist regime in Germany in the 1930s. He was enthusiastically welcomed in Turkey and appointed as the Chief of the First Surgery Clinic in Istanbul University in 1933. He worked with discipline and in cooperation with his Turkish colleagues, such as Ahmed Burhaneddin Toker, Fahri Arel, Dervis Manizade, and others, who were to become the leading authorities of general thoracic surgery in Turkey. During his 6 years of residence and working in Istanbul, he contributed highly to the practice of general and thoracic surgery. He had to leave for the United States in 1939 for treatment of his lung abscess due to a retained bullet from World War I. He stayed in New York and later in Basel until his death. He was presented an honorary professorship from Hacettepe University, Ankara in 1973. (C) 2000 by The Society of Thoracic Surgeons.
Keywords: 15TH-CENTURY